The development of novel antimicrobial peptides with activity against MRSA - Pritchard, Kevin (2008)
MRSA is a significant pathogen, which can cause a range of minor and major infections both in the hospital and community environments. MRSA is developing resistance to many antibiotics, including vancomycin, which is now the first choice antibiotic to treat MRSA infections in the UK. This together with the dearth of new antibiotics being introduced could see the emergence of untreatable S. aureus strains. This has led to renewed interest in alternative antimicrobial agents.